Desentralisasi sebagai Upaya Pembangunan Desa secara Menyeluruh Menurut UU No. 6 Tahun 2014 - Khoiriza N., Muhammad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
Various regulations have been issued by the government to develop the village since 1948 by Law No. 22 on Local Government. The final rule is Law No. 6 of 2014 on the Village. The genesis of Law No. 6 of 2014 is the embodiment of a decentralized system. This paper intends  to  explain  how  the  decentralization  system  provided  by  Law No. 6 of 2014 gives effect to undertake rural development as a whole. Through this legislation anyway been delegated from thecentral state to local governments to lead to the village government can be realized. With the delegation of authority from the central government to village government,  the  village  government  has  the  power  to  manage  all matters  relating  to  his  village  and  ended  up  giving  a  significant influence in the development  of the  village. Nevertheless,  the overall rural development may occur when leader and staff of the village can create policies that impact on rural development which is determined according to the priorities in the Minister of Rural No.5 of 2015.